High altitude mining workers anthropometry - Ramírez, Augusto V. (2006)
Introduction: Anthropometry is the essential basis for ergonomics, mainly human body’s measures referred to size and shapes. Peruvian mining is located at high altitudes, habitat of ethnic Andean men showing different anthropometry to the sea level man. Objectives: To characterize anthropometrics of a Peruvian Andean Mountain mining workers, native men population, residing and living at 3 000 masl and more. Design: Descriptive, prospective and observational study. Setting: La Oroya Centromin-Peru Enterprise’s Occupational Health Service and its four mining satellite hospitals. Participants: Three thousand healthy native 21 to 60 year-old male mining workers residing in altitudes above 3 500 masl. Interventions: The sample was generated by conglomerate’s random aleatory polyphase model. The study was done between 1984-1994. For normality hypothesis statistical certainty we applied Shapiro – Wilk’s two tails significant test. Main outcome measures: Morphologic, macroscopic, phenotypic and surface measurements done with a measurement protocol and according to a scientific recognized technique. Results: Highlighted parameters were: standing, stature 151,2 to 154,6, floor-eyes height, 1,481 m; sitting, chair-elbow 0,243 m, to vertex and eye height, 1,155 and 1,095 m; hand, width and length, 0,104 to 0,171 m; foot, width and length, 0,92 and 0,239 m; thoracic perimeter, resting 98,16, forced inspiration, 105,3, forced espiration, 94,3 cm. Results were validated with Shapiro Wilk’s test that values x between 0,01 and 0,099. From the whole (47), three parameters were totally rejected: arm maximum vertical reach, hip width and cranium perimeter, whose parameters x value was >0,50. Conclusions: The Andean miner worker has proper dimensions different from the sea level man. Integral anthropometric and ergonomics parameters investigations on high altitude living Andean workers should be carried out.